Analysis of Rice Business Income in Samaturu District, Kolaka Regency - Irmawati irmawati; La Nalefo La Nalefo; Muhamad Syukri Sadimantara (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
The aims of this study are: (a) To analyze the income of rice farmers in Kaloloa Village, Samaturu District, Kolaka Regency; (b) To analyze the strengths, weaknesses, opportunities, and threats in Manage Village, Samaturu District, Kolaka Regency, and (c) To study the rice marketing strategy in Kaloloa Village, Samaturu District, Kolaka Regency. This Research will be conducted in November 2019 in Kaloloa Village, Samaturu District, Kolaka Regency. The population in this study were all rice farmers in Kaloloa Village, Samaturu District, Kolaka Regency, which amounted to 13 rice farmers. The sample in this study is part of the number and characteristics possessed by the population. In this study, the sample for internal factors consisted of 13 rice farmers, and the sample for external factors consisted of 3 consumers. Analysis of the data used in the Analysis of the Principal Opportunity Point (BEP) used to determine the strategy. This study shows that rice farmers in Kaloloa Village have an average production of 4,146 with a selling price of Rp. 4,500/Kg. So farmers' income is IDR 91,471,900 / season or equivalent to an average of 7,036,300. per season. Meanwhile, the total production is 20,025, with an average of 4,146 per hectare.